Enhanced Oxidative Stress Is Responsible for TRPV4-Induced Neurotoxicity - Hong, Zhiwen; Tian, Yujing; Yuan, Yibiao; Qi, Mengwen; Li, Yingchun; Du, Yimei; Chen, Lei; Chen, Ling (Frontiers in Cellular Neuroscience, 2016)
Transient receptor potential vanilloid 4 (TRPV4) has been reported to be responsible for neuronal injury in pathological conditions. Excessive oxidative stress can lead to neuronal damage, and activation of TRPV4 increases the production of reactive oxygen species and nitric oxide (NO) in many types of cells. The present study explored whether TRPV4-induced neuronal injury is mediated through enhancing oxidative stress. We found that intracerebroventricular injection of the TRPV4 agonist GSK1016790A increased the content of methane dicarboxylic aldehyde (MDA) and NO in the hippocampus, which was blocked by administration of the TRPV4 specific antagonist HC-067047. The activities of catalase (CAT) and glutathione peroxidase (GSH-Px) were decreased by GSK1016790A, whereas the activity of superoxide dismutase remained unchanged. Moreover, the protein level and activity of neuronal nitric oxide synthase (nNOS) were increased by GSK1016790A, and the GSK1016790A-induced increase in NO content was blocked by an nNOS specific antagonist ARL-17477. The GSK1016790A-induced modulations of CAT, GSH-Px and nNOS activities and the protein level of nNOS were significantly inhibited by HC-067047. Finally, GSK1016790A-induced neuronal death and apoptosis in the hippocampal CA1 area were markedly attenuated by administration of a reactive oxygen species scavenger Trolox or ARL-17477. We conclude that activation of TRPV4 enhances oxidative stress by inhibiting CAT and GSH-Px and increasing nNOS, which is responsible, at least in part, for TRPV4-induced neurotoxicity.